Dekonstruksi Ideologi Pancasila sebagai Bentuk Sistem Hukum di Indonesia - Achmad Hariri (Universitas Serang Raya, 2019)
Pancasila legal system in Indonesia does not seem to have found a final formulation, it is still abstracted from the dominant legal system, namely civil law / rechstaat. In the 1945 Constitution it is clear that Indonesia promulgates as a legal state, although there is no implicit explanation of the legal system which is adopted (rechstaat, the rule of law or the Pancasila legal system), on the other hand Pancasila becomes the ideology and basis of the state, therefore there needs to be a formulation of the Indonesian legal system by deconstructing (reading; dismantling) the Pancasila ideology, so that the Pancasila is not only an ideology, but also as a legal system adopted in Indonesia. Pancasila can be placed in a prismatic postulate, where Pancasila is placed as a counterweight between existing legal systems, the Pancasila legal system can be used as an alternative legal system originating from noble values, legal systems relevant to plural societies are legal pluralism, namely common law configurations who uphold substantive justice, civil law that knows procedural justice, and the Pancasila legal system that upholds social justice. so that the substance of prismatic Pancasila law can be realized, namely justice as its purpose.